Lateral position preference in grazing feral horses. (4th October 2019) - Inoue, Sota; Yamamoto, Shinya; Ringhofer, Monamie; Mendonça, Renata S.; Hirata, Satoshi
Abstract: Behavioural lateralisation is an effective way for animals to manage daily tasks by specialising behaviour to either side of the body. Many types of lateralisation are linked to the function of each brain hemisphere. Lateralisation of monitoring behaviour in mother–infant relationships occurs in a wide range of mammals, where infants frequently use their left eye to monitor their mother. However, few studies have focused on this type of spatial relationships among adults in daily life, such as during foraging. The present study focused on monitoring adult feral horse behaviour using quantitative analysis of spatial relationships, using drone technology. We found that horses form a localised spatial relationship with their nearest neighbour. Specifically, the nearest neighbour was located to the left rear of a target individual significantly more frequently than to the right rear. Furthermore, the nearest neighbour was less frequently located behind a target individual. We propose that this relationship is caused by a left‐eye preference, because information via the left eye predominantly proceeds to the right hemisphere, which is dominant for social processing.